2002
DOI: 10.1016/s0016-7037(02)00928-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mn oxides on the reduction of uranium(VI) by the metal-reducing bacterium Shewanella putrefaciens

Abstract: Influence of Mn oxides on the reduction of uranium(VI) by the Influence of Mn oxides on the reduction of uranium(VI) by the metal-reducing bacterium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
129
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(143 citation statements)
references
References 69 publications
12
129
1
1
Order By: Relevance
“…Manganese oxides are also relatively strong oxidants and can oxidize insoluble, reduced contaminants such as the mineral uraniniteðUO 2 Þ ðsÞ , a common product of microbial uranium reduction . Fredrickson et al (2002) Liu et al 2002). The oxidation of biogenic UO 2(s) coupled with b-MnO 2(s) reduction is well-described by an electrochemical model .…”
Section: Transport and Redox Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manganese oxides are also relatively strong oxidants and can oxidize insoluble, reduced contaminants such as the mineral uraniniteðUO 2 Þ ðsÞ , a common product of microbial uranium reduction . Fredrickson et al (2002) Liu et al 2002). The oxidation of biogenic UO 2(s) coupled with b-MnO 2(s) reduction is well-described by an electrochemical model .…”
Section: Transport and Redox Reactionsmentioning
confidence: 99%
“…The presence of Mn(III/IV) oxides has been shown to impede the formation of Fe(II) by dissimilatory metal reducing bacteria (DMRB) (Myers & Nealson 1988), probably via the rapid oxidation of biogenic Fe(II) (Myers & Nealson 1988). Although the extent to which Mn(III/IV) and Fe(III) oxides may jointly affect the in situ microbial reduction of U(VI) is unknown, it is clear that metal reduction and mineral precipitation processes at the cellular level as described by Fredrickson et al (2002) and Liu et al (2002) can have an important role.…”
Section: Transport and Redox Reactionsmentioning
confidence: 99%
“…Also listed in Table 3 Although we demonstrated that U(IV) reoxidation became thermodynamically favorable in these reducing soils, the TEA(s) have not been identified. and Mn(IV) oxides to oxidize U(IV) in the presence of electron shuttles has been shown 27,28 , and soluble Fe(III) has been found in the pore waters of reduced sedimentary material containing crystalline and/or amorphous Fe-oxides 29 .…”
mentioning
confidence: 99%
“…The abiological oxidation of U(IV) is coupled to the reduction of O 2 , Fe(III), and Mn(IV) (Langmuir, 1978;Nevin and Lovley, 2000;Wielinga et al, 2000;Fredrickson et al, 2002;Liu et al, 2002). These inorganic reactions are kinetically fast and proceed without any surface catalysts.…”
Section: Abiological Processes That Control U Redox Transformationsmentioning
confidence: 99%